2014
DOI: 10.1111/ijsw.12139
|View full text |Cite
|
Sign up to set email alerts
|

Identity reconstruction as shiduers: Narratives from Chinese older adults who lost their only child

Abstract: Identity reconstruction as shiduers:Narratives from Chinese older adults who lost their only child Zheng Y., Lawson T.R. Identity reconstruction as shiduers: Narratives from Chinese older adults who lost their only childThe purpose of this qualitative study was to illustrate how the identity of Chinese older adults who lost their only child changed after the traumatic event in the context of unique culture and policy settings. The individuals studied were 14 adults over the age of 50. Each respondent was inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(83 citation statements)
references
References 45 publications
1
82
0
Order By: Relevance
“…Besides, research indicated that parents in one-child families demonstrate "child-centeredness" significantly more than parents in multiple-child families 21 . Losing the only child often means losing their main source of care-giving, hope for the future, a great threat to the individual's well-being, and consequences of declining mental health or social withdrawal, which may progress to a point of social isolation because communicating about their child's death is often difficult and can be hurtful and stigmatizing 22 . The dominant Confucian philosophy regard death as a negative event in life 23 ; it makes death a taboo topic which hinders acceptance of grief counseling or other forms of professional intervention.…”
Section: Dilemma Of Sdp In Chinamentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, research indicated that parents in one-child families demonstrate "child-centeredness" significantly more than parents in multiple-child families 21 . Losing the only child often means losing their main source of care-giving, hope for the future, a great threat to the individual's well-being, and consequences of declining mental health or social withdrawal, which may progress to a point of social isolation because communicating about their child's death is often difficult and can be hurtful and stigmatizing 22 . The dominant Confucian philosophy regard death as a negative event in life 23 ; it makes death a taboo topic which hinders acceptance of grief counseling or other forms of professional intervention.…”
Section: Dilemma Of Sdp In Chinamentioning
confidence: 99%
“…The Chinese government has taken measures to mitigate the policy's negative effects. However, these measures are mostly focused on material supports, including increasing the national standard subsidy for parents of the lost only child but studies showed that the increasing subsidy and other financial aids did not improve the situation of SDP where they were deemed as a social identity culturally stigmatized and politically victimized 22 . Some of Shidu parents rejected to receive the financial aids as they didn't want to be pitied for the lose of their children and felt stigmatized for the discontinuity of their family.…”
Section: Dilemma Of Sdp In Chinamentioning
confidence: 99%
“…Therefore, the QOL score of shidu parents was much lower than that of the general population in China. The loss of an only child often meant the loss of their primary source of health care, the end of family continuity, and a signi cant hazard to personal happiness [40]. For Chinese shidu parents, certain unique factors impacted their physical and mental health.…”
Section: Mediation Analyses Resultsmentioning
confidence: 99%
“…Correlations between the CBSQ subscales and subscales of the GCQ and PG-13 highlight these links. For example, grief beliefs related to filial piety were strongly related to negative beliefs about the self, which may contribute to a diminished confidence in one's coping abilities, and consequently cause feelings of inferiority and helplessness (Zheng & Lawson, 2014). Stigmatizing perceptions and beliefs about destiny were related to negative beliefs about the self, life, future, and threatening grief interpretations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the destiny culture is deeply engrained in Chinese culture (He et al, 2014). Shidu parents often identify with other parents who lost their only child as Tong Ming Ren, which means 'those who share the same destiny' (Zheng & Lawson, 2014). Fate and destiny beliefs such as 'Fate comes and gathers, but fate goes and scatters' (Liu, 2011) are common spiritual beliefs of the Chinese stemming from both Confucianism (Steven & Li, 1987), and Buddhism (Guang, 2013).…”
Section: Introductionmentioning
confidence: 99%